Challenges of IFIs in practicing IFM and their solutions: Evidence from Islamic banks and insurance companies (IIUC Business Review, 2021)
This research aimed to explore the challenges and solutions in practicing Islamic Financial Management (IFM) in Islamic Financial Institutions (IFIs) in Bangladesh. To achieve the objectives, this study adopted the qualitative approach and purposive sampling method including twenty-five semi-structured interviews with managers of Islamic banks and Islamic insurances. The rich qualitative data from the interviews were thematically analysed to identify the challenges and solutions in practicing IFM in the IFIs in Bangladesh. The major challenges and solutions that emerged were mainly categorised into three main types: social, organisational, and individual challenges and solutions. However, some of these challenges have been consistent with the previous studies while some have been newly identified from the participants' opinions. Similarly, some of the solutions in practicing IFM in the IFIs have been similar to the previous studies, while some of the findings have emerged as new additions to the current literature and practice. The results of the study have significant implications for both literature and practice.IIUC Business Review Vol. 10, Dec. 2021 pp. 43-68